The Relationship between Age, Education, and Maternal Employment with Exclusive Breastfeeding in Children Aged 6 - 23 Months in Kalirejo, Malang Regency - Ramadhanti, Nanda Amalia; Farid, Muhammad Rifqo Hafidzudin; Fadila, Salma; Naziliah, Adristi Hanun; Febriyani, Putu Laksmi; Gabriella, Clarisa Christina; Hewiz, Alya Shafira (SAFE-Network, 2023)
The target percentage of infants under 6 months old receiving exclusive breastfeeding is 40%. However, in 2020, in Kalirejo Sub-district, the number was 9.04%. This was presumably caused by the high number of working mothers. Therefore, this study was conducted to analyze the relationship between age, education, and occupation of mothers regarding exclusive breastfeeding in children aged 6-23 months in Kalirejo Sub-district, Malang Regency. The study design employed in this research was observational analytics with a cross-sectional design. The research population consisted of mothers residing in Kalirejo Sub-district, Malang Regency. The required sample size was 66 individuals. A questionnaire was used to collect research data. The required data was processed using SPSS software with the Chi-Square Test analysis technique. The result showed that 78.8% mothers were in the age group of 20-35%, and 21.2% were in the age group of >35 years. Based on the highest education level attained by the respondents, 1.5% had completed elementary school, 15.2% had completed junior high school, 57.6% had completed high school, and 25.8% had completed tertiary education. About 51.5% of respondents were employed, while 48.5% were not employed. The number of respondents' children receiving exclusive breastfeeding was 50%. The analysis indicated a relationship between occupation and exclusive breastfeeding with a p-value of 0.049 and a strength of relationship between the two variables at 0.236.